2014
DOI: 10.1371/journal.pone.0110155
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Formation and Solution Properties of Worm-Like Micelles Formed Using Both N-Hexadecyl-N-Methylpiperidinium Bromide-Based Cationic Surfactant and Anionic Surfactant

Abstract: The viscoelastic properties of worm-like micelles formed by mixing the cationic surfactant N-hexadecyl-N-methylpiperidinium bromide (C16MDB) with the anionic surfactant sodium laurate (SL) in aqueous solutions were investigated using rheological measurements. The effects of sodium laurate and temperature on the worm-like micelles and the mechanism of the observed shear thinning phenomenon and pseudoplastic behavior were systematically investigated. Additionally, cryogenic transmission electron microscopy image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
(28 reference statements)
1
1
0
Order By: Relevance
“…We also observed fingerprint-like patterns [Fig. 3(i)], which resemble previously published images of surfactant micelles (Wei et al, 2016;Yan et al, 2014). However, no intact crystals were observed.…”
Section: Ns-tem Imaging Of Lipid Phasessupporting
confidence: 88%
“…We also observed fingerprint-like patterns [Fig. 3(i)], which resemble previously published images of surfactant micelles (Wei et al, 2016;Yan et al, 2014). However, no intact crystals were observed.…”
Section: Ns-tem Imaging Of Lipid Phasessupporting
confidence: 88%
“…The simple phase diagram revealed that for a wide range of molar ratios, the aggregates formed by C18-DQA and SL efficiently increased the viscoelasticity of the solutions, an unprecedented observation compared to previously reported wormlike micelle systems constructed with SL and other cationic surfactants. 35,36 As shown in Fig. 3, at a fixed C18-DQA concentration, the zero-shear viscosity of the mixed solutions increased with increasing the molar ratio of SL : C18-DQA, indicating an optimized molecular geometry for forming wormlike micelles.…”
Section: Resultsmentioning
confidence: 83%